The Formalism in Mortgage Accordance of Amarican Law - Abdul Hussein, Russul Ghani Abdul Hussein; Bashat, Jalil (Journal of Legal Sciences, 2023)
This research deals with the formalities of the mortgage contract according to American law, We have given an overview of the provisions of this law related to the subject, We have also taken into consideration the role of American jurisprudence and the judiciary in finding legal solutions to the aforementioned formality, We have discussed the formality of mortgage in American law in two sections, In the first section we showed the formalism in immovable mortgage, and the second section specified to studying the formalism in movable mortgage.